Carbon dioxide capture and storage scenarios: a case study of the East Midlands and Yorkshire (UK). (6th August 2009) - Gough, Clair; Bentham, Michelle; Shackley, Simon; Holloway, Sam
This paper uses quantitative electricity supply scenarios to explore the potential for CO2 storage at locations in the Southern North Sea basin from point sources within a case study region that consists of the East Midlands combined with Yorkshire and Humberside in the UK. The reactions to these scenarios from a variety of stakeholders from the public and private sectors are explored using an assessment process. The scenarios demonstrate that there is sufficient storage capacity within reservoirs in the Southern North Sea basin for CO2 generated within the region's power stations to 2050 and beyond, even under a high fossil fuel scenario. Carbon dioxide Capture and Storage (CCS) was typically seen as offering significant potential for CO2 mitigation by a small but varied selection of professional stakeholders, although the consensus over the preferred approach to a low carbon electricity supply was far from evident.